The bank capital requirements in the SSM: a supervisory approach - Costa, Luís Filipe Gouveia Machado e (2021)
The financial and supervisory data collection and analysis of the 128 significant institutions of the SSM shows that in 2017, on average, European banks were operating with a considerable excess regulatory total capital ratio. Although this might empirically challenge part of the literature – according to which banks would tend to operate with as much leverage as they are allowed to – a more granular analysis shows that despite the level playing field envisaged by the Banking Union, there are still statistically significant national differences among Pillar 2 capital add-ons, which were expected to address strictly idiosyncratic risks of institutions.